PATHOGENETIC MECHANISMS OF ENDOTHELIAL DYSFUNCTION IN WORKERS EMPLOYED IN THE ENVIRONMENT WITH LOW CONCENTRATIONS OF LEAD - Charles, A.; Яворовський, О.П.; Шейман, Б.С. (World of Medicine and Biology, 2014)
The paper presents the results of examination of employees which professionally contacting with lead. Toxemia formation at a heavy degree has been detected. The basic mechanisms of toxemia formation, the size of molecules and particles of endotoxins, potential of toxin-induced cytolytic activity (TITSA), the priority sites for of endotoxins accumulation on toxin-carrying blood fractions depending on the level of lead in the blood have been defined. Excessive contents of nitrite-nitrate in serum (NO 2- / NO3-) of surveyed workers, that was accompanied by the accumulation of content S-nitrozotiols (RS --NO +) and dynitrozyl iron complexes ((RS-) 2Fe + (NO +) 2) have been established. It is recommended to define the content of nitrite-nitrate amount (NO 2- / NO3-) and its stable metabolites (S-nitrozotiols (RS --NO +) and dynitrozyl iron complexes ((RS-) 2Fe + (NO +) 2) in serum as markers of early diagnosis of vazotoxic effects of lead. Its role in the formation of endothelial dysfunction in lead intoxication was defined.
Keywords: lead; nitrate; nitrite; S-nitrozotiole; dinitrosyl iron complexes; Markers; diagnosis; prevention; endotoxemia; mechanisms of formation